Analysis of Narcotics Circulation in Riau Province; inherited and studied in the View of Criminology Integrative Theory - Kasmanto Rinaldi; Rio Tutrianto; Muhamad Fazil bin Ahmad; M. Zulherawan (Faculty of Law, Universitas Pekalongan, 2023)
The rise of narcotics smuggling in Indonesia is a complex issue that requires a comprehensive explanation. The use of integration theory, specifically the integration of Cultural Transmission and Differential Association, can provide a better understanding of the phenomenon of narcotics crime in urban areas. Cultural Transmission theory suggests that individuals learn their values, beliefs, and behaviors through the process of socialization within their culture. This theory highlights the role of family, peer groups, and the media in shaping an individual's attitudes and behaviors towards drugs. The theory argues that individuals who are exposed to drug use at an early age are more likely to engage in drug use themselves. On the other hand, Differential Association theory suggests that individuals learn deviant behaviors from their associations with others. The theory posits that individuals who associate with those who engage in deviant behavior, such as drug use, are more likely to adopt those behaviors themselves. By integrating these two theories, we can better understand the complex phenomenon of narcotics crime in Indonesia. The use of rat ports as entry points for illegal drugs can be explained by the influence of cultural transmission, where individuals are exposed to drug use through their socialization process. Furthermore, the use of these rat ports can also be explained by differential association, where individuals who associate with drug smugglers are more likely to engage in the smuggling of narcotics themselves. Overall, the integration of Cultural Transmission and Differential Association theory provides a more nuanced understanding of the complex phenomenon of narcotics crime in Indonesia. By considering the various factors that contribute to the rise of narcotics smuggling, we can develop more effective strategies to combat this issue.